Fluid Restriction for Treatment of "Fluid Creep" after Acute Burn Resuscitation. Issue 4 (July 2014) - Tang, YW; Chen, IC; Yen, JH; Lu, CT; Lai, CS; Liu, HJ; Chang, HC; Chen, YW
Objective: Fluid creep in patients recovering from acute burns still exists, despite the use of a more treatment conservative approach. Most of our severe burn patients develop fluid overload and body weight increase after acute fluid resuscitation. How to quickly return patients to their pre-injury body weight is an important issue. Methods: Right after acute fluid resuscitation, we applied a "total fluid requirement" volume (usually 1/2 to 2/3 of initial 24 hour volume) and strictly monitored patients' hourly urine (between 0.5-1 ml/kg/hr). Patients' responses (body weight, enteric feeding amount, pulmonary condition, etc.) were also closely monitored and frequent adjustments of fluid volume administration were performed simultaneously. Results: Most patients regained their pre-injury body weight within 2-3 weeks. Enteric feeding also improved markedly. No patients had severe oedema-related complications. Conclusions: Stricter fluid administration after acute burn fluid resuscitation is advised for allowing patients to reduce body weight to their pre-injury weight or at least close to it. We use pre-injury body weight, enteric feeding and urine output as our guides. (Hong Kong j.emerg.med. 2014;21:222-229)